Remembering Islam: A Critique of Habermas and Foucault (American Journal of Islam and Society, 1989)
IntroductionJean Baudrillard suggested we "forget Foucault" because his status asone of the greatest thinkers of the West in this century belied his commitmentagainst state power. A similar criticism may be levied against Habermas,whose ideal communication community merely reproduces and perpetuatesso-called modern secular Western epistemologies. If we take seriously theanarchic thought of Habermas and Foucault, we conclude that theepistemologies created in the past few hundred years are pernicious, pervasive,and truth-distorting. But their vision of the possible world which wouldemerge after the death of these epistemologies is extremely restricted andinadequate. I suggest we "remember" Islam as the divine guidance of God(SWT), which provides the basis for a truly emancipatory meta-critique. Theextension of an Islamic critique into the realm of anarchic thought gives itmore precision and sophistication.Social and Natural Sciences: The Islamic Perspective [1981] lays thefoundation for an Islamic critique of Western episternologies and the rebuildingof the Islamic sciences by exposing the inadequacies of Western epistemologiesand by outlining the guidelines along which Islamic epistemologies must directthe intellectual power of Muslim scholars. The contributors to Social andNatural Sciences denounce the modernized and socialized versions of Islamarising in this century. These versions borrowed their essence not from Islambut from the capitalist, neo-colonial West or from the Marxist-Leninist East.I suggest we characterize the first part of this Islamic critical endeavor asanarchic in that it recognizes the Western epistemologies are neither benignnor local, but in fact carry interest-full, imperialist, dominating designs on ...